1996
DOI: 10.1128/jb.178.13.3934-3938.1996
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic analysis of Helicobacter pylori by multilocus enzyme electrophoresis: extensive allelic diversity and recombinational population structure

Abstract: Genetic diversity and relationships in 74 Helicobacter pylori isolates recovered from patients assigned to distinct clinical categories were estimated by examination of allelic variation in six genes encoding metabolic housekeeping enzymes by multilocus enzyme electrophoresis. Seventy-three distinct allele profiles, representing multilocus chromosomal genotypes, were identified. All six loci were highly polymorphic, with an average of 11.2 alleles per locus. The mean genetic diversity in the sample was 0.735, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
134
3
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(149 citation statements)
references
References 63 publications
8
134
3
4
Order By: Relevance
“…Several investigations have suggested that genetic diversity and substantial heterogeneity of H pylori has major contribution in pathogenesis of this bacterium, as each genotype leads to different type of diseases (Go et al, 1996;Marshall et al, 1996). For instance, cagA gene of H pylori is revealed to be involved in pathogenesis of Gastric cancer (Graham and Yamaoka, 1998;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have suggested that genetic diversity and substantial heterogeneity of H pylori has major contribution in pathogenesis of this bacterium, as each genotype leads to different type of diseases (Go et al, 1996;Marshall et al, 1996). For instance, cagA gene of H pylori is revealed to be involved in pathogenesis of Gastric cancer (Graham and Yamaoka, 1998;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as the antibodies react with defined antigens, the test allows the simultaneous detection of bacterium virulence factors. However, as there is a high degree of genetic heterogeneity among H. pylori strains and, consequently, in the proteins that are surface-exposed or secreted (Go et al 1996, Herbrink & van Doorn 2000, the assay must be validated for the population being studied (Mitchell et al 1996, Aucher et al 1998, Yamaoka et al 1998, Figueiredo et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Isolados clínicos obtidos de diferentes pacientes têm mostrado grande diversidade genética (25,34) . Nesse sentido, estudos baseados nas seqüências genômicas de duas cepas de H. pylori (26695 e J99) revelaram que 22% dos genes não são essenciais e aproximadamente 6% são únicos a cada linhagem (7,50) .…”
Section: Introductionunclassified
“…Atualmente, o microrganismo é considerado o mais importante agente causador de gastrite, fator essencial na gênese da úlcera péptica e fator de risco para o desenvolvimento de câncer gástrico (19) . Há, ainda, evidências de sua associação com o linfoma MALT (linfoma do tecido linfóide associado à mucosa) e com o linfoma não-Hodgkin gástrico (15) .Isolados clínicos obtidos de diferentes pacientes têm mostrado grande diversidade genética (25,34) . Nesse sentido, estudos baseados nas seqüências genômicas de duas cepas de H. pylori (26695 e J99) revelaram que 22% dos genes não são essenciais e aproximadamente 6% são únicos a cada linhagem (7,50) .…”
unclassified